Evaluating Elementary School Principals’ Digital Leadership in Managing Students’ Generative AI Use - Amarulloh Amarulloh; Nur Ridha Utami; Undang Rosidin; Rabiyatul Adawiyah Siregar; Handoko Handoko (STKIP Al Islam Tunas Bangsa dan HEPI, 2026)
This study evaluated principals' digital leadership in managing students' generative Artificial Intelligence (GenAI) use in elementary schools using the Context, Input, Process, and Product (CIPP) evaluation model. A qualitative evaluation study was conducted in an Indonesian public elementary school involving one principal, two vice principals, five classroom teachers, three parent representatives, and two students. Data were collected through semi-structured interviews, observations, and document analysis and analyzed using the interactive model of Miles, Huberman, and Saldaña. The results indicated an urgent need for school-level GenAI governance. Existing digital infrastructure, teacher readiness, and parental support provided a foundation for implementation, while principals enacted digital leadership through policy communication, teacher empowerment, monitoring practices, and stakeholder collaboration. These efforts contributed to strengthening students' awareness of responsible GenAI use and enhancing digital literacy. The study was limited to a single-school context and qualitative evidence. Schools should strengthen AI-related professional development, parental engagement, and age-appropriate governance frameworks. This study extends the application of the CIPP model to GenAI governance and highlights principals' digital leadership as a key mechanism for fostering responsible AI use in elementary education.